Digital Transformation in Culture: Current Realities and Development Perspectives - Олена Гудзенко (Cхід, 2024)
The article is devoted to innovative aspects of digital transformation in the sphere of culture. The author examines the impact of new products, innovative business models and digital technologies on the modern cultural landscape. Special attention is paid to the role of digital platforms in the interaction of the sphere of exchange of values and information in the context of digital art. The article notes that digital transformation is becoming a key catalyst for innovation in the cultural and artistic environment, creating opportunities for the preservation and promotion of national cultural values. The author considers various approaches to digital transformation, taking into account both a strategic partnership and a comprehensive approach, as well as the dynamics of the interaction of technologies, directions, and participants in the process of achieving new forms of activity and increasing efficiency in business. In addition, the article highlights the problems that arise during the digital transformation of objects of art and cultural heritage, in particular, such as the provision of property and copyright rights, as well as the inconsistency of terminology between information and digital cultures. The author points to the need for a new scientific discourse on digital rights for the successful implementation of digital transformation in the sphere of culture in Ukraine. The article examines the individual challenges and prospects of digital transformation for the museum industry and also emphasizes the need to create the necessary conditions for each museum separately. The author examines the influence of digital technologies on the museum sphere, providing concrete examples of the implementation of innovations (creation of museum digital collections, virtual exhibitions and tours). Based on the relevance of digital transformation in the modern world, attention is drawn to the need to improve the qualifications and awareness of specialists in the field of culture for the successful implementation of digital initiatives.